Young adults’ perceptions of adverse childhood experiences as context and causes of mental health conditions: Observations from the United States - Kathryn Sabella; Ian A. Lane; Murron O'Neill; Natalie Tincknell (Child Protection and Practice)
Background: The relationship between adverse childhood experiences (ACEs) and mental health later in life has been well-established. However, first-person qualitative narratives describing how ACEs negatively impact mental health of young adults are rare. Objective: Qualitative data explores how young adults with serious mental health conditions (SMHC) describe childhood adversities and relate those experiences to their mental health conditions. Participants and setting: Young adult participants (n = 55; ages 25–30) who self-reported being diagnosed with an SMHC were recruited from one state in United States. In-person interviews were conducted to gather narratives related to mental health, education, training, and employment. Methods: Young adults with lived experience actively participated in the research process. Iterative coding and thematic analysis were employed to assess ACEs reported and analyze how participants described those experiences as influential. Results: Most participants identified as White, non-Hispanic women. Major depression and anxiety disorders were the most prevalent diagnoses. Over 80% reported experiencing trauma, familial mental illness, or substance use challenges. Young adults connected their ACEs to fear and anxiety, emotional processing difficulties, poor coping behaviors, delayed help-seeking, and later negative interpersonal relationships. Conclusions: This study is the first to qualitatively describe how young adults with SMHC describe ACEs and relate those experiences to their own mental health conditions. Future research should seek similar first-hand accounts in vulnerable populations and consider the unique impact of the COVID-19 pandemic. Findings and future research can inform policy, practice, and mental health treatment for young adults who have experienced ACEs, especially in the post-pandemic era.